2003
DOI: 10.1074/jbc.m301196200
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for an Intracellular ADP-ribosyl Cyclase/NAD+-glycohydrolase in Brain from CD38-deficient Mice

Abstract: Cyclic ADP-ribose, a metabolite of NAD؉ , is known to modulate intracellular calcium levels and signaling in various cell types, including neural cells. The enzymes responsible for producing cyclic ADP-ribose in the cytoplasm of mammalian cells remain unknown; however, two mammalian enzymes that are capable of producing cyclic ADP-ribose extracellularly have been identified, CD38 and CD157. The present study investigated whether an ADP-ribosyl cyclase/NAD ؉ -glycohydrolase independent of CD38 is present in bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
63
1
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 43 publications
6
63
1
4
Order By: Relevance
“…This seemingly contradictory result may be explained by the possibility that CD38-independent ADP-ribosyl cyclase can compensate the loss of CD38 to produce normal levels of cADPR, thereby contributing to the normal Ca 21 handling properties of these neurons. Along this line, it has been reported previously that an intracellular membrane-bound ADP-ribosyl cyclase/NAD 1 -glycohydrolase distinct from CD38 is expressed in mouse brain, and the novel enzyme is more active in the developing brain than in the adult tissue [27]. Thus, the search and identification of CD38-independent ADP-ribosyl cyclase must continue.…”
Section: Discussionmentioning
confidence: 93%
“…This seemingly contradictory result may be explained by the possibility that CD38-independent ADP-ribosyl cyclase can compensate the loss of CD38 to produce normal levels of cADPR, thereby contributing to the normal Ca 21 handling properties of these neurons. Along this line, it has been reported previously that an intracellular membrane-bound ADP-ribosyl cyclase/NAD 1 -glycohydrolase distinct from CD38 is expressed in mouse brain, and the novel enzyme is more active in the developing brain than in the adult tissue [27]. Thus, the search and identification of CD38-independent ADP-ribosyl cyclase must continue.…”
Section: Discussionmentioning
confidence: 93%
“…Investigators have reported ADP-ribosyl cyclase activity that is independent of CD38 (69). The non-CD38 ADP-ribosyl cyclase activity has been reported in brain homogenates obtained from CD38 knockout mice (69). However, CD38 is reported to be the only ADP-ribosyl cyclase present in the ASM (47).…”
Section: Adp-ribosyl Cyclase Cd38 and Cyclic Adp-ribose In Airway Smentioning
confidence: 99%
“…Mounting evidence has indicated that ADPR-cyclase(s) other than CD38 may exist in the kidney, brain, and the heart (40,45), including various cells (30,(45)(46)(47). The first clues to the existence of novel ADPR-cyclase(s) emerged from experiments of the comparison of tissue cADPR levels in CD38 wild type and knockout mice (40).…”
Section: Diabetic Nephropathy and The Renin-angiotensin-aldosterone Smentioning
confidence: 99%